Argon Plasma Coagulation for Extraction of an Impacted Trapezoid Basket in the Pancreatic Duct. Issue 3 (April 2015) - Purohit, Treta; Garg, Mrinal; Kulkarni, Abhijit; Thakkar, Shyam
Abstract : N/A: We performed endoscopic retrograde cholangiopancreatography (ERCP) with sphincterotomy for pancreatic stent placement on a 55‐year‐old woman with a dilated pancreatic duct, pancreatic duct stone, and chronic pancreatitis. During follow‐up ERCP, the lithotripter traction wire fractured during electrohydraulic lithotripsy and mechanical lithotripsy. Multiple attempts using standard techniques to clear the lithotripter and stone failed. Argon plasma coagulation (APC) was used to ablate 2 of the lithotripter wires, and the lithotripter was disengaged from the stone and removed.